Respuesta :

Answer:

x + 1/3

Step-by-step explanation:

It just basically the average of the three expressions

=> Remember to divide the expressions into 2 groups (the x group which contains x in it, and the numeral group which doesn't contains x)

The x group: (4x + 7x + (-8x)) /3 = x

The numeral group: (5 +(-6) + 2) /3 = 1/3

So the answer must be x + 1/3, not x + 1

(I hope this is helpful)

Answer:

second option

Step-by-step explanation:

the average is calculated as

average = [tex]\frac{sum}{count}[/tex]

              = [tex]\frac{4x+5+7x-6-8x+2}{3}[/tex]

              = [tex]\frac{3x+1}{3}[/tex]

              = [tex]\frac{3x}{3}[/tex] + [tex]\frac{1}{3}[/tex]

              = x + [tex]\frac{1}{3}[/tex]